The 'magnificent castle' of Culzean and the Kennedy family - Moss, Michael S. (Edinburgh University Press, 2002)
Culzean Castle on the Ayrshire coast is the most visited property of the National Trust for Scotland. This lavishly illustrated book tells the whole history of the castle.